Study on the clinical efficacy and safety of baloxavir marboxil tablets in the treatment of influenza A - Qiu, Chaochao; Cheng, Fang; Ye, Xinchun; Wu, Zhengxing; Ning, Hongye; Liu, Saiduo; Wu, Lianpeng; Zhang, Yiyang; Shi, Jichan; Jiang, Xiangao (Frontiers in Medicine, 2024)
Objective To evaluate the clinical efficacy and safety of baloxavir marboxil tablets in the treatment of influenza A. Method According to a random sequence generated by computer software, 200 patients with confirmed influenza A were divided into a study group and a control group with 100 cases in each group. Group allocation was concealed using sealed envelopes. The study group was treated with oral administration of baloxavir marboxil tablets, 40 mg once. The control group was given oral oseltamivir capsules, 75 mg twice a day, for five consecutive days. The therapeutic effects, symptom disappearance time and adverse drug reactions of the two groups after five days of treatment were compared. Result There was no significant difference in the total effective rate between the two groups (99% vs 98%, P > 0.05). There was no significant difference in fever subsidence time (1.54 ± 0.66 d vs 1.67 ± 0.71 d, P > 0.05), cough improvement time (2.26 ± 0.91 d vs 2.30 ± 0.90 d, P > 0.05) and sore throat improvement time (2.06 ± 0.86 d vs 2.09 ± 0.83 d, P > 0.05) between the two groups. There was no significant difference in the incidence of adverse drug reactions between the two groups (8% vs 13%, P > 0.05).Baloxavir marboxil tablets can be effectively used in the treatment of patients with influenza A and have a similar efficacy and safety profile as oseltamivir capsules.